Gene Kelly : The Making of a Creative Legend - Hess, Earl J.; Dabholkar, Pratibha A. (Book collections on Project MUSE., 2020)
"Gene Kelly (1912-1996) was a multi-faceted entertainer whose large fan following views him primarily as a dancer on the big screen. Most people fail to realize that Kelly was a renaissance man--dancer, choreographer, actor, singer, director, teacher-whose career stretched from Broadway musicals in the late 1930s through his domination of the Golden Age of the Hollywood musical in the 1940s and 1950s to television and radio into the 1980s. Yet Kelly's career, unique as it is, has never been given the treatment it deserves: his previous biographers have produced generic narratives about his life and work based on limited research, relying heavily on secondary sources and interviews, and ignoring archival material. Gene Kelly is a completely different kind of biography of Kelly than what has been produced thus far-one based on thorough research in which the authors chart and analyze the trajectories in Kelly's life and career and assess his accomplishments within the wider context of American culture. Hess and Dabholkar not only consulted the vast number of books and articles on Kelly, dance, film, and Hollywood; they conducted extensive archival research, making use of, among other collections, transcriptions of interviews by and about Kelly, Kelly's personal papers, and the papers of several people who worked with him"--